Adult-onset Nemaline Myopathy Coexisting With Myasthenia Gravis: A Case Report. Issue 4 (January 2016) - Cao, Lingling; Wang, Yanling; Liu, Xiaofeng; Hu, Yanxia; Li, Nianchun; Qiu, Guoping; Luo, Yun; Li, Weidong
Abstract : Abstract: Myasthenia gravis (MG) is an autoimmune neuromuscular junction disorder which is characterized by fluctuating muscle fatigue. However, the association of MG with nemaline myopathy is rarely reported. Here we report a case of MG coexisting with adult-onset nemaline myopathy. A 55-year-old man endured fluctuating muscle weakness with positive acetylcholine receptor and titin antibodies. After the patient was administrated cholinergic drugs and immunosuppression, the muscle weakness of the patient had mildly been alleviated. Electromyography showed a progressive decrement in the amplitude of muscle action potential at low frequency. Muscle biopsy showed numerous nemalines in the muscle fibers. This is the first reported case of nemalines present in the muscle fibers of adult patient with MG. The pathogenesis of nemaline may be related to titin antibody in adult-onset nemaline myopathy with MG.